Detection Rate, Anatomic Sites, and Pathologic Types of Colorectal Cancer During Colonoscopy Procedures. Issue 5 (October 2017) - Liu, Lan; Zhu, Kongxi; Yu, Weihua; Zhang, Shanyan; Teng, Guoxin; Guo, Jianqiang
Abstract : Purpose: This study aims to help physicians obtain the detection rate and colonoscopic information of colorectal cancer (CRC) among patients in a city in China. Methods: A total of 15, 189 participants who underwent total colonoscopy between January 2000 and December 2015 were studied. A total of 1022 CRCs were diagnosed. We analyzed the detection rate, anatomic sites, and pathologic types among different sex, age, and decade groups. Moreover, we investigated the corresponding relationships between the anatomic sites and the pathologic types. Results: Colonoscopic examinations revealed that the risk for CRC between men and women showed no significant difference (6.97% vs. 6.42%). The detection rate of CRC significantly increased with age (2.08% vs. 5.95% vs. 15.09%). The proportion of poorly differentiated adenocarcinoma among the youth group was significantly higher than that in the other age groups (25.0% vs. 11.54% vs. 8.33%). However, the numbers of cases with well-differentiated and moderately differentiated adenocarcinoma observed in the old-aged group were higher than other age groups. This finding demonstrated that the differentiation degree of adenocarcinoma increased with the age. Neuroendocrine tumor was mainly located in the rectum (95.0%), and appeared more frequently among the youth group (7.5% vs. 1.48% vs. 1.06%). Conclusions: We found the detection rate of CRC varied in terms of sex and decade. The CRC cases in the youth group exhibited a high malignant degree. The most common anatomic site was rectum, so we should focus more on digital rectal examination.